Evolution of the Population Structure of Staphylococcus pseudintermedius in France - Bergot, Marine; Martins-Simoes, Patricia; Kilian, Hélène; Châtre, Pierre; Worthing, Kate A.; Norris, Jacqueline M.; Madec, Jean-Yves; Laurent, Frédéric; Haenni, Marisa (Frontiers in Microbiology, 2018)
Staphylococcus pseudintermedius is a colonizer as well as an important pathogen of dogs where it is responsible for skin, ear and post-operative infections. The emergence of methicillin-resistant S. pseudintermedius (MRSP) in the early 2000s, which were additionally resistant to most veterinary-licensed antibiotics, drew specific attention to these pathogens due to the limitations created in veterinary therapeutic options. Multiple studies showed that the sequence type (ST)71 was the most frequently identified clone in Europe. A few years ago, several publications have suggested a decline of the ST71 clone and the emergence of the ST258 lineage in Northern Europe. In this study, we show that ST71 is also decreasing over time in France and that the non-ST71 population is highly heterogeneous. Globally, the non-ST71 clones are more susceptible to antibiotics, which might be good news for veterinarians. Two other lineages, ST258 and ST496, seem to be successful in France. These isolates, as well as representatives of the ST71 clone, underwent whole-genome sequence. This study shows that the ST71 and ST496 clusters are highly homogenous while the ST258 cluster is more diverse. Each ST possesses a specific pattern of resistance and virulence genes. The reasons for the apparent and simultaneous success of the ST258 and ST496 clones remain unclear. But the emergence of the ST496 clone will require monitoring given its multi-resistant genotype and threat to canine health.